2021
DOI: 10.1097/spv.0000000000000719
|View full text |Cite
|
Sign up to set email alerts
|

Does Rectocele on Defecography Equate to Rectocele on Physical Examination in Patients With Defecatory Symptoms?

Abstract: Objectives Our primary objective was to determine the association between rectocele size on defecography and physical examination in symptomatic patients. Our secondary objective was to describe the associations between both defecography and physical examination findings with defecatory symptoms and progression to surgical repair of rectocele. Methods We performed a retrospective review of all patients referred to a female pelvic medicine and reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…However, it is also possible that this small difference suggests that these 2 groups represent 2 distinct phenotypes. This is consistent with a retrospective cohort study published by Wallace et al 22 in 2019 that found that evidence of a rectocele on defecography does not necessarily associate with PVWP on examination in patients with defecatory symptoms. Thus, there are 2 possible explanations for this finding: one is that women with prolapse and radiographic rectoceles represent a different phenotype or possibility that there is a continuum of prolapse development where women without clinical prolapse are on an early spectrum of that continuum.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is also possible that this small difference suggests that these 2 groups represent 2 distinct phenotypes. This is consistent with a retrospective cohort study published by Wallace et al 22 in 2019 that found that evidence of a rectocele on defecography does not necessarily associate with PVWP on examination in patients with defecatory symptoms. Thus, there are 2 possible explanations for this finding: one is that women with prolapse and radiographic rectoceles represent a different phenotype or possibility that there is a continuum of prolapse development where women without clinical prolapse are on an early spectrum of that continuum.…”
Section: Discussionsupporting
confidence: 92%
“…Such postdefecation images may also reveal features of pelvic organ prolapse (e.g., enterocele or peritoneocele) that may not be evident on images during defecation (Figure). Barium trapping was more frequently observed with larger rectoceles in some 23,26 but not all studies 20 . Moreover, barium trapping does not predict the outcome after rectocele repair 27,28 .…”
Section: Diagnosis and Classificationmentioning
confidence: 92%
“…Barium trapping was more frequently observed with larger rectoceles in some 23,26 but not all studies. 20 Moreover, barium trapping does not predict the outcome after rectocele repair. 27,28 Hence, the utility of this feature to identify patients for surgery is unclear.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging, such as dynamic magnetic resonance imaging, has been evaluated in comparison with physical examination, but fluoroscopic defecography has not yet been standardized for the evaluation of pelvic organ prolapse 4,5 . A single-center retrospective review failed to show a correlation between rectocele size on defecography and physical examination 6 …”
mentioning
confidence: 99%